1997
DOI: 10.1126/science.278.5339.838
|View full text |Cite
|
Sign up to set email alerts
|

Mesoporous Platinum Films from Lyotropic Liquid Crystalline Phases

Abstract: symmetries in the finite-difference grid. For example, the fault-parallel components of the velocity as well as the normal and an shear stresses are antisymmetric, whereas the fault-perpendicular component of the velocity and the uyx and a , stresses are symmetric across a vertical fault in the xz plane. By careful examination of the numerical implementation, it can be shown that, if the numerical values of the velocity and stress have the aforementioned symmetries about the fault plane at the Nth time step, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
637
0
8

Year Published

1998
1998
2013
2013

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 943 publications
(662 citation statements)
references
References 20 publications
17
637
0
8
Order By: Relevance
“…In particular, they showed that the reduction of platinum salts in this system led to Pt whose nanostructure was a cast of LLC phase architecture. Such granular nanostructured metals could be directly used in catalysis, but they were of limited relevance for the electrochemical or sensor devices in which the metal was required as a thin film [58].…”
Section: Mesoporous Metals and Alloysmentioning
confidence: 99%
“…In particular, they showed that the reduction of platinum salts in this system led to Pt whose nanostructure was a cast of LLC phase architecture. Such granular nanostructured metals could be directly used in catalysis, but they were of limited relevance for the electrochemical or sensor devices in which the metal was required as a thin film [58].…”
Section: Mesoporous Metals and Alloysmentioning
confidence: 99%
“…Casting such structures -which have aspect ratios One way to make templates on the nanometrescale exploits the amphiphilic nature of soaps: lyotropic liquid crystals self-assemble depending on solvent concentration and temperature into an astonishing array of soft nanostructures. Sol-gel or electrodeposition in only the aqueous compartments of the structure are used to cast templates, resulting in nanomaterials that are impossible to produce in any other way 8,9 (Fig. 2b).…”
Section: Commentarymentioning
confidence: 99%
“…A cationic assembly can exchange its counteranion, for example, chloride, with a mineralizable inorganic anion, protonated silicate. Synthesis of mesoporous thin films [7,14,18,[21][22][23]29], spheres [17,30,31], curved shaped solids [16,18], tubes [24,32], rods and fibers [18,33], membranes [34], and monoliths [35] has been reported recently. While chemistry of this process is rather well understood, the mechanism of formation of nanoporous silica shapes is not well elaborated.…”
Section: Introductionmentioning
confidence: 99%